Can the Positive and Negative Syndrome scale (PANSS) differentiate treatment-resistant from non-treatment-resistant schizophrenia? A factor analytic investigation based on data from the Pattern cohort study. (June 2019) - Freitas, Rosana; dos Santos, Bernardo; Altamura, Carlo; Bernasconi, Corrado; Corral, Ricardo; Evans, Jonathan; Malla, Ashok; Krebs, Marie-Odile; Nordstroem, Anna-Lena; Zink, Mathias; Haro, Josep Maria; Elkis, Helio
Highlights: Treatment-Resistant Schizophrenia (TRS) may represent a distinct subtype of schizophrenia, with a different symptom profile. However, there are no studies which compared patients with TRS with non-TRS regarding this aspect. Using data from a large cohort of patients with schizophrenia of pattern 8 countries study, we compared 409 patients with TRS with 1209 non-TRS by either by exploratory as well as confirmatory factor analyses. Both groups showed almost identical factorial structure, but the model yielded proved to have a satisfactory fit when compared with previous well-known factorial models of the PANSS. Abstract: Treatment-Resistant Schizophrenia (TRS) and Non-Treatment-Resistant Schizophrenia (NTRS) may represent different subtypes of schizophrenia. However, few studies have investigated their PANSS symptom dimensions by Exploratory (EFA) or Confirmatory (CFA). Data from the present study are derived from 1429 patients of the Pattern study. TRS was defined by the use of clozapine in the previous year whereas NTRS by the use of non-clozapine antipsychotics ("by proxy"). Factors were chosen based on the Kaiser criterion and considered valid when loadings were greater than or equal to 0.5. The fit to the data was evaluated by CFA in comparison with well-established PANSS models, using fit indexes. The EFA yielded similar five-factor model in both groups: Negative, Positive, Anxiety/Depression, Cognitive and Excited. CFA showed a satisfactory, but not perfect, fit to the data, as compared with the previous PANSS factor analytic models. Despite the limitations regarding the 'by proxy' definition of TRS, the results of the present study show that there are no differences in the factorial structure of PANSS in patients with TRS and NTRS.